Renewable H2 from Glycerol Steam Reforming: Effect of La2O3 and CeO2 Addition to Pt/Al2O3 catalysts. - Montini, Tiziano (2010)
Glycerol is the main byproduct of biodiesel production and its increased production volume derives from the increasing demand for biofuels. The conversion of glycerol to hydrogenrich mixtures presents an attractive route towards sustainable biodiesel production. Here we explored the use of Pt/Al2O3-based catalysts for the catalytic steam reforming of glycerol, evidencing the influence of La2O3 and CeO2 doping on the catalyst activity and selectivity. The addition of the latter metal oxide to a Pt/Al2O3 catalyst is found to significantly improve the glycerol steam reforming, with high H2 and CO2 productions. A good catalytic stability is achieved for the Pt/La2O3/Al2O3 system working at 3508C, while the Pt/CeO2/Al2O3 catalyst sharply deactivates after 20 h under similar conditions.Studies carried out on fresh and exhausted catalysts reveal that both systems maintain high surface areas and high Pt dispersions. Therefore, the observed catalyst deactivation can be attributed to coke deposition on the active sites throughout the catalytic process and only marginally to Pt nanoparticle sintering. This work suggests that an appropriate support composition is mandatory for preparing high-performance Ptbased catalysts for the sustainable conversion of glycerol into syngas.